Demand-driven forecasting : a structured approach to forecasting - Chase, Charles (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
An updated new edition of the comprehensive guide to better business forecasting Many companies still look at quantitative forecasting methods with suspicion, but a new awareness is emerging across many industries as more businesses and professionals recognize the value of integrating demand data (point-of-sale and syndicated scanner data) into the forecasting process. Demand-Driven Forecasting equips you with solutions that can sense, shape, and predict future demand using highly sophisticated methods and tools. From a review of the most basic forecasting methods to the most a.
Analysis of the Autocorrelation Plots.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Economic forecasting; Business forecasting; Forecasting; Business forecasting; Economic forecasting; Forecasting; BUSINESS & ECONOMICS -- Economics -- Theory; Business forecasting; Economic forecasting; Forecasting; Electronic books; Electronic books